THE ROLE OF BEYOND CONNECTIVITY IN TRANSACTION COSTS ON THE SUCCESS OF MSME BUSINESS INCUBATION - Noriska, Ni Komang Septia (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
Ministry of Cooperatives and MSMEs data shows that Micro, Small, and Medium Enterprises (MSMEs) contribute significantly to Indonesia's economy, contributing approximately 61% of the total Gross Domestic Product (GDP) in 2022 and absorbing up to 97% of the workforce across various sectors. Along with the rapid development of information and communication technology (ICT), the concept of Beyond Connectivity emerges as a potential solution to overcome the challenge of high transaction costs in MSMEs. This concept not only connects businesses with consumers digitally but also key in improving operational efficiency and significantly reducing transaction costs. This research uses a quantitative approach with a true experimental method and 2x2x2 factorial design, involving 30 MSME participants working in technology and non-technology fields. The main focus is to explore the role of technology as a moderating variable that influences the relationship between transaction costs and MSME business success. The research results are expected to provide new empirical contributions that expand understanding of technology's strategic function in the MSME context, going beyond previous studies that mostly highlighted technology's direct impact on MSME operations without considering the interaction between technology and transaction costs. These findings open opportunities for developing more effective policies and business strategies to support MSME growth and competitiveness in the digital era. The originality of this research lies in the technology moderation approach to transaction costs in the MSME context and the use of strong factorial experimental design, providing new empirical contributions and practical implications for MSME development in the digital era.